2014
DOI: 10.1002/ange.201402767
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Tunable Chemoselective N Functionalization of Indoles with Ynamides

Abstract: Two unprecedented N functionalizations of indoles with ynamides are described. By varying the electron‐withdrawing group on the ynamide nitrogen atom, either Z‐indolo‐etheneamides or indolo‐amidines can be selectively obtained under the same metal‐free reaction conditions. The scope and synthetic potential of these reactions, as well as some mechanistic insights provided by DFT calculations, are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…[19] Using sodium tert-butoxide in dimethylformamide triggered thec leavage of the electron-with-drawing group to give phenylketenimine 3,p resumably throught he intermediacy of sodium indolide as the nucleophile. [19] Using sodium tert-butoxide in dimethylformamide triggered thec leavage of the electron-with-drawing group to give phenylketenimine 3,p resumably throught he intermediacy of sodium indolide as the nucleophile.…”
Section: Scheme21 Synthesis Of Stablesilyl-keteniminesmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Using sodium tert-butoxide in dimethylformamide triggered thec leavage of the electron-with-drawing group to give phenylketenimine 3,p resumably throught he intermediacy of sodium indolide as the nucleophile. [19] Using sodium tert-butoxide in dimethylformamide triggered thec leavage of the electron-with-drawing group to give phenylketenimine 3,p resumably throught he intermediacy of sodium indolide as the nucleophile.…”
Section: Scheme21 Synthesis Of Stablesilyl-keteniminesmentioning
confidence: 99%
“…For their part, Dodd and Cariou studied the reaction between indoles andu nsubstituted ynamides 72 under basic conditions (Scheme 25). [19] Using sodium tert-butoxide in dimethylformamide triggered thec leavage of the electron-with-drawing group to give phenylketenimine 3,p resumably throught he intermediacy of sodium indolide as the nucleophile. [20] Addition of the anion to the ethenimine then led to indolic amidine 73 in good yields that vary depending on the nature of the electron-withdrawing group.…”
Section: Base-mediated Transformationsmentioning
confidence: 99%
“…However,d irect application of our previously disclosed reaction conditions [4] -namely 1.0 equiv of ynamide, 1.0equiv of t-BuONa as base, DMF as solvent, and with molecular sieves at RT-proved to be totally ineffective, even after prolonged reaction time ( Table 1, entry 1). We reasonedt hat the cycloaddition process required thermal activation and although traditional heating (entry 2) was unsuccessful, using microwave conditions [11] allowed the reaction to take place (entry 3).…”
mentioning
confidence: 98%
“…[2] We have shown that under strongly basic conditions [3] an unprecedented nucleophilic addition of various heteroarenes at the b positionc ould take place. [4] Moreover,d epending on the substitution pattern of the nitrogen atom, the same basic conditions could lead to an a-nucleophilic addition, albeit with the loss of the electron-withdrawing group (EWG). In the a-nucleophilic addition case, base activation would lead to cleavage of the EWG, forminga na mide that would eventually evolvet oward ketenimine 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation